2018
DOI: 10.1038/s41598-018-21425-7
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 contributes to the development of gout and hyperuricemia in a genome-wide association study

Abstract: Although many genome-wide association studies (GWASs) of hyperuricemia or gout have been reported, the related genetic factors and the mechanisms from hyperuricemia to gouty attack remain unclear. This study aimed to identify genetic factors and pathogenesis of gout from hyperuricemia by genome-wide association study (GWAS). 747 gout patients, 747 hyperuricemia and 2071 age-matched controls were recruited and analyzed with Affymetrix 650 K chip to find the related genetic variants. The functions of the related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 44 publications
(42 reference statements)
6
44
0
5
Order By: Relevance
“…Deficiency in ABCG2 generates dysfunctional mitochondria [25] and reduced copy number of mitochondrial DNA associates with increased risk of gout in NZ Polynesian [26]. The observation that colchicine is able to rescue the 141K trafficking defect [23], the proposal that autophagy machinery and the inflammasome interact in the innate immune response [27], and evidence for association of ABCG2 rs2231142 with gout in the presence of HU in East Asian populations [28][29][30], suggests that ABCG2 may be important in gout beyond its established role in elevating urate levels. This hypothesis is further supported by the observation that the effect size of ABCG2 on urate in Europeans and Japanese is 58% and 73% that of SLC2A9, the most influential urate locus [4,31], respectively, yet the effect size of ABCG2 on gout is consistently larger than that of SLC2A9 [4,5,32].…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency in ABCG2 generates dysfunctional mitochondria [25] and reduced copy number of mitochondrial DNA associates with increased risk of gout in NZ Polynesian [26]. The observation that colchicine is able to rescue the 141K trafficking defect [23], the proposal that autophagy machinery and the inflammasome interact in the innate immune response [27], and evidence for association of ABCG2 rs2231142 with gout in the presence of HU in East Asian populations [28][29][30], suggests that ABCG2 may be important in gout beyond its established role in elevating urate levels. This hypothesis is further supported by the observation that the effect size of ABCG2 on urate in Europeans and Japanese is 58% and 73% that of SLC2A9, the most influential urate locus [4,31], respectively, yet the effect size of ABCG2 on gout is consistently larger than that of SLC2A9 [4,5,32].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the SNP was direction‐consistent with gout in both white and black participants (Dehghan et al, ). Subsequent genetic studies in other populations, such as Han Chinese (Yang et al, ; Chen et al, ), Japanese (Matsuo et al, ), and Caucasians (Zhang et al, ), provided compelling evidences for the association of ABCG2 with the susceptibility of hyperuricemia. Recently, the study of Abcg2 ‐knockout mice has revealed that the extra‐renal urate excretion decrease induced by ABCG2 dysfunction also caused hyperuricemia (Ichida et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a Taiwanese study of people with gout, the 141K allele was associated with tophi in both Han and Aboriginal Taiwanese populations (Cleophas et al, 2017). The polymorphism rs2231142 in the ABCG2 gene, which causes a Glu141Lys amino acid substitution, accounted for 0.57% of the variation in serum urate, and a functional study of rs2231142 showed that it causes a 53% reduction in the rate of ABCG2-mediated urate transport compared with wildtype ABCG2 (Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%